Studi Eksegetis tentang "Haustafel" dalam Kolose 3:18-21 - Ramayani Nggadas (Views : Jurnal Teologi dan Biblika, 2023)
Abstract: This study is a biblical study or exegesis of the text in Colossians 3:18-21 that focuses on the expression of haustafel. Before presenting an interpretation of the above text, there are two specific issues of background to be discussed first, namely: the origin of the haustafel in Paul's letters and the purpose of Paul presenting the hautafel in the context of the Colossians. The study uses qualitative methods for the interaction of its sources. For the elaboration of the topic and its texts, the researchers use a biblical approach, the method of historical grammatical exegesis. By applying the method, the researcher discusses both the lateral aspects and the grammar of the original text of Colossians 3:18-21 to interpret the text in its original context. The results of this study confirm that (1) the Haustafel in the Colossians reflect that the rules concerning the relations between family members were a common thing at the time. (2) the haustafel of the Colosos, although showing some similarity with the hautafel in Greek and Jewish context, must be deemed to have originated from Paul himself in order to correct the teachings and influence of the dogmas circulating in the congregation of Coloses. (3) the Hautafel is Paul's affirmation that life in the Spirit does not exclude responsibility and differences in the role of each member of the family.  Abstrak: Penelitian ini merupakan kajian biblika atau eksegesis terhadap teks dalam Kolose 3:18-21 yang difokuskan pada ungkapan haustafel. Sebelum mengemukakan tafsiran terhadap teks di atas, ada dua isu spesifik yang bersifat latar belakang yang akan dibahas terlebih dahulu, yaitu: asal-usul haustafel dalam surat-surat Paulus dan tujuan Paulus mengemukakan haustafel dalam konteks surat Kolose. Penelitian ini menggunakan metode kualitatif untuk interaksi sumber-sumbernya. Untuk elaborasi topik serta teks acuannya, peneliti menggunakan pendekatan biblika yaitu metode eksegesis gramatika historis. Dengan menerapkan metode peneliti membahas tentang aspek kesejarahan maupun tata bahasa teks acuannya yaitu Kolose 3:18-21 guna menafsirkan teks ini dalam konteks originalnya. Ada pun hasil penelitian ini menegaskan bahwa (1) Haustafel dalam surat Kolose mencerminkan bahwa aturan-aturan mengenai relasi antar-anggota keluarga merupakan sesuatu yang umum pada waktu itu. (2) Haustafel dalam surat Kolose meskipun memperlihatkan beberapa kemiripan dengan haustafel dalam konteks Yunani Romawi dan Yahudi, namun mesti dianggap berasal dari Paulus sendiri dalam rangka mengoreksi ajaran serta pengaruh dari ajaran bidat yang beredar di jemaat Kolose. (3) Haustafel tersebut merupakan penegasan Paulus bahwa kehidupan di dalam Roh tidak meniadakan tanggung jawab serta perbedaan peran dari setiap anggota keluarga.